The Mind language - Bull, Peter; Ducat, Vivian; Hutton, Richard; Levis, Kenneth (The Mind series, 1988)
Language is unique to the human mind. Focusing on the special human phenomenon of speech this episode explores different theories on the evolution of language. One theory is that language is the result of gene mutation resulting in quantum leaps in the normal evolutionary process. You'll witness experiments that reveal an infant's innate drive to communicate. Scientists show that linguistic capacity is present even without speech or hearing.